Concrete slabs strips reinforced with epoxy-bonded carbon laminates into slits - Bonaldo, Everaldo (2005)
A promising strengthening strategy, using carbon fiber reinforced polymer (CFRP) materials, consists in applying CFRP laminate strips into pre-cut slits opened in the concrete cover of the elements to strengthen. Since both faces of the laminate are bonded to concrete by epoxy adhesive, the maximum attainable strain in the CFRP at the failure of the strengthened element is higher than when the CFRP is externally bonded. This strengthening technique is designated by Near Surface Mounted and has been successfully used to increase the flexural and the shear resistance of concrete and masonry structures. In the present work, the effectiveness of this technique to increase the service and ultimate load carrying capacity of reinforced concrete slabs is assessed by an experimental program. A numerical strategy was developed to predict the load-deflection relationship of this type of elements. The results are presented and analyzed, and the performance of the numerical model is appraised.